2015
DOI: 10.1111/josi.12152
|View full text |Cite
|
Sign up to set email alerts
|

Talking Up and Talking Down: The Power of Positive Speaking

Abstract: Consistent with Lewin's legacy and SPSSI's traditions, out work has focused on in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…To the best of our knowledge, this is the first research to demonstrate that exposure to the positive components of complementary gender stereotypes can induce participants with stereotype threat. These findings offer a novel integration between the stereotype threat literature (see Steele et al ., ) and research on the compensatory nature of stereotypes (Fiske et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first research to demonstrate that exposure to the positive components of complementary gender stereotypes can induce participants with stereotype threat. These findings offer a novel integration between the stereotype threat literature (see Steele et al ., ) and research on the compensatory nature of stereotypes (Fiske et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The present research puts forward the argument that, besides their contribution to legitimizing traditional gender roles, an additional means through which complementary gender stereotypes reinforce these roles is by undermining women's and men's performance in negatively stereotyped domains. This argument is based on findings which show that negative stereotypes can be activated through reminders of complementary positive stereotypes (Fiske et al ., ). Specifically, research on the ‘innuendo effect’ (Kervyn, Bergsieker, & Fiske, ) has found that when participants are exposed to descriptions of social targets that focus on their positive traits (e.g., describing a target as high on warmth), they interpret these descriptions as implying complementary negative information as well (e.g., that the target is also low on competence).…”
Section: Introductionmentioning
confidence: 97%
“…Polite language can also be used to examine status differences (Miller, Rye, Wu, Schmer-Galunder, & Ott, 2014). Polite language involves the expression of positive emotions and frequent use of hedges, indirect language, and counterfactual language (Danescu-Niculescu-Mizil, Sudhof, Jurafsky, Leskovec, & Potts, 2013), which is coupled with infrequent use of negative language and little expression of negative emotions (Fiske et al, 2015). Generally, lower status group members use polite language more frequently than do higher status group members (E.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also likely to be effective when stereotypes about a group are ambivalent. For example, Fiske et al (2015) found that if an outgroup is viewed ambivalently, listeners continue to infer the negative dimension even when it is omitted from communication.…”
Section: Literature Reviewmentioning
confidence: 99%